Prevalence and barriers of menstrual hygiene practices among women of reproductive age group in rural field practice areas of a tertiary care center in Rishikesh - Bhavana Saini; Meenakshi Khapre; Prakash Kumar; Ranjan Bharadwaj; Anupam Gupta; Santosh Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Menstruation is a natural, physiological process experienced by all adolescent girls and women. The reproductive age group is the largest and most susceptible to various health and illness-related risk factors. This study aims to find the prevalence of satisfactory menstrual hygiene management (MHM) among women of reproductive age group and we also want to explore the cultural practices and beliefs related to menstruation and barriers to satisfactory MHM. Material and Methods: This study was conducted in rural field practice areas of Department of Community and Family Medicine , AIIMS, Rishikesh including 271 participants; women of reproductive age group using a mixed method study design (sequential quan-qual). Quantitative data were collected by household surveys and government schools using a validated structured questionnaire. Descriptive statistics were used to analyze the data. Focus group discussions (FGD) were conducted to have insights about understanding menstrual hygiene and barriers to satisfactory hygiene practices. Results: It was found that only 70 (29.6%) participants adhered to satisfactory menstrual hygiene practices. The age group of 20-24 years had a higher proportion compared to other groups. Through FGD, the main themes derived were practices related to menstruation (maintenance of personal hygiene), daily activities (physical and mental problems during menses), and barriers faced (cultural, economic, privacy concerns, and shyness). Conclusion: The prevalence of satisfactory menstrual hygiene practices was very low only 29.6%, which is a cause of concern; either Taboos associated with menstruation, socio-cultural, economic barriers, or lack of awareness related to menstrual hygiene in the community can be contributing factors for low prevalence.